Faktor Pengaruh Kesehatan Lingkungan terhadap Kejadian Demam BerdarahDangue (DBD) di Wilayah Endemis: Systematic Literature Review - Lestari, Peggy Ayu; Fajar, Nur Alam; Windusari, Yuanita; Novrikasari; Sunarsih, Elvi (Health Information : Jurnal Penelitian, 2023)
One of the environment-based diseases is Dengue Fever, which is currently a public health problem due to the rapid spread of the disease and the potential for death. Indonesia is a DHF endemic area and this disease is still a major problem since the disease was first detected in Jakarta and Surabaya in 1968. The transmission of DHF can be influenced by environmental factors. The purpose of this study was to determine what environmental factors affect the incidence of DHF. This research used a literature review method obtained through searching journals from Google Search or Google Scholar, PubMed and Elsevier. There was an association of environmental factors such as (rainfall, air temperature, air humidity, population density, airy ventilation and lighting) on the incidence of DHF.